Optimal Dispatching of Changzhou Water Conservancy Project During Flood Seasons Based on Different Needs - HUANG Feng; HOU Guibing; LI Yuanyuan; WANG Baohua (Renmin Zhujiang)
In view of the increasingly prominent contradiction between flood control and water supply and demand in the Changzhou Water Conservancy Project,the current dispatching scheme of the reservoir is analyzed from the aspects of water supply,power generation,shipping,and ecology,and the comprehensive dispatching requirements are proposed.In addition,modern forecasting and dispatching technologies are used to systematically study the optimal dispatching scheme under different dispatching needs.The operating water level during the flood season is increased from 18.6 m to 19.6 m,and the risk and benefit are analyzed.The results show that the implementation of the scheme can increase the water level of the reservoir area by 1.0~1.5 m and the water storage capacity by 200 million cubic meters on the premise of ensuring flood control safety.The scheme gives full play to the water supply,shipping,and ecological benefits of the reservoir,and meanwhile,it can raise the power generation capacity by 5.05%,producing remarkable economic and social benefits.